Amelia Bedelia 4 mayor - Herman Parish (Mexico Scholastic INC, 1999)
The race is on! Amelia Bedelia always does what she's told. So when Mr. Rogers tells her she should run for Mayor Thomas's office, she picks up her shirt, and dashes off to City Hall. She knows just what she'd do in the mayor's shoes (polish them, of course). With Amelis Bedelia in the race, politics will never be the same!
Keywords: Fiction -- Fiction